Treatment experiences and preferences of British South Asians living with recurrent depression - Amirah Akhtar; Shabana Shafiq; Sahdia Parveen; Emmanuel Nwofe; Karen Windle (PLoS ONE, 2026)
Introduction Depression is one of the leading causes of disability and is a highly recurrent condition. Recurrent depression has been associated with risk of suicide and greater morbidity. British South Asians are at greater risk of developing depression and face greater barriers to help-seeking and treatment uptake. To better support this population and reduce the risk of relapse it is important to explore treatment experiences and preferences. Aims This study explored the treatment experiences and preferences of 12 British South Asians living with recurrent depression. Methods We conducted semi-structured interviews and analysed the data using thematic analysis. Results Pharmacological treatments were accompanied by a continuous lay evaluation process of the pros and cons. A preference for non-pharmacological interventions was found, particularly art-based, creative approaches. Interventions that were culturally adapted, with incorporation of religion were preferred. Barriers to recovery included inexperienced therapists and lack of support post-intervention to maintain durable effects of therapy. Discussion Health professionals, such as general practitioners and therapists, play a key role in shared decision making, to ensure people with recurrent depression feel supported and culturally appropriate treatment is offered. Managing recurrent depression, including reducing the risk of relapse can improve quality of life, wellbeing and reduce the risk of co-morbid conditions.